Disasters in conflict areas: finding the politics. (16th August 2018) - Siddiqi, Ayesha
Abstract : Despite some 50 years of research, relatively little is known about how disasters in conflict areas are created and discursively framed, and how information on them is publicly consumed. The emphasis in disaster studies has remained on establishing causal linkages, demonstrating the way in which natural hazard‐related disasters result in deepening conflict, or ushering in peace. Furthermore, it has been accepted that disaster risk reduction is the state's responsibility. The strengths and limitations of these approaches are examined prior to a political reimagining of disasters in conflict areas. The absence of 'politics' from the wider debate on disasters in conflict areas is not just a benign oversight, but is in fact the politics of disasters in conflict areas. A politics that does not engage with the processes and outcomes of pursuing dominant agendas, such as neoliberal orthodoxy and state imperial control, in areas and communities vulnerable to natural hazards and political conflict needs to be recognised and challenged.